Isolation and Characterization of a Probiotic Bacillus sp. from Donkey Milk and Its Microencapsulation for Enhanced Gastrointestinal Delivery - Ramar, Rajesh Kannan; Revathi, K.; Devi, R.; Rajadesingu, Suriyaprakash; Palani, Naveen; Kaasi, Vaithianathan; Prabakaran; Sandhya (International Journal of Aquatic Research and Environmental Studies, 2026)
Probiotics should have strong attributes to survive across the gastrointestinal tract and be able to colonize. Improving the probiotic stability and targeted delivery remains the major challenge for functional food development. The present paper extracted probiotic bacteria from donkey (Equus asinus) milk, identified their functional features, and generated an encapsulation system that presented better stability and loading.Two Gram positive, catalase-positive bacterial strains were isolated using MRS medium and evaluated for probiotic properties, including auto-aggregation, cell surface hydrophobicity, antimicrobial activity, acid tolerance, and resistance to the simulated gastric fluid. The selected strain was identified as Bacillus sp. Microencapsulation was performed using an alginate-xanthan gum matrix by the extrusion method. Encapsulation efficacy, capsule morphology, storage stability, release kinetics in stimulated intestinal fluid, and in vitro toxicity were assessed. Bacillus sp.exhibited superior probiotic properties, including auto-aggregation (69.34%), cell surface hydrophobicity (59.4%), DPPH radical scavenging activity (85%), acid tolerance with only a 0.57-log reduction at pH 3, and strong antimicrobial activity against Serratia sp., Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae. The optimized formulation (10% sodium alginate, 1.5% xanthan gum) achieved 91% encapsulation efficiency and produced spherical capsules of about 3000 mm diameter. Encapsulated cells showed 3.7-log improved survival in simulated gastric fluid at pH 2.0 and 3.03-log higher viability after 50 days of refrigerated storage. PH-responsive release resulted in near complete cell liberation within 4 h in simulated intestinal fluid. In vitro cytotoxicity assay confirmed formulation safety. The developed xanthan gum encapsulation system significantly enhances probiotic survival, storage stability, and targeted intestinal delivery.